Illness and culture in the postmodern age - Morris, David B. (Berkeley : University of California Press, 1998)
The author of this book argues that postmodern illness is created at the interconnection of biology and culture. Morris analyzes the distinctive experience of illness in our time, taking cultural studies into a new area called 'biocultural' studies.
Country of the ill -- What is postmodern illness -- White noise of health -- Reinventing pain -- Utopian bodies -- Neurobiology and the obscene -- Plot of suffering -- Illness in the time of Disney.
Includes bibliographical references (pages 279-333) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Diseases -- Social aspects; Social medicine -- Philosophy; Postmodernism; Social medicine; Ethnology; Medicine -- Philosophy; Disease -- psychology; Sociology, Medical; Ethnology; Anthropology, Cultural; Philosophy, Medical; Social Medicine; Sociologie de la santé.; Postmodernisme; Sociologie médicale.; Ethnologie; Médecine -- Philosophie; Médecine sociale; social anthropology; ethnology; 44.06 medical sociology; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; MEDICAL / Diseases; Social medicine; Medicine -- Philosophy; Ethnology; Diseases -- Social aspects; Postmodernism; Social medicine -- Philosophy; Ziekten; Cultuur; Postmodernisme